Effect of pH and agitation time on combustible recovery and ash rejection in a coal sample using selective hydrophobic coagulation (2018)
(Eng) This paper shows the effect of pH and agitation time (Agt) on combustible recovery and ash rejection for a Colombian bituminous coal sample from Cerrejón (La Guajira), using a Selective Hydrophobic Coagulation process. A 2 2 factorial central composite experimental design was used, varying the pH and the agitation time as entry variables. The sample was processes in a specially built coagulation cell. The results show that the selectivity of the process is highest in a pH range of 4 to 10, with ash rejection values above of 70%. The statistical analysis showed that pH is a variable that has a significant effect (95% confidence level) in the selective hydrophobic coagulation process, while the agitation time has no significance effect.